Lysine Acetyltransferase Inhibitors From Natural Sources - Fiorentino, Francesco; Mai, Antonello; Rotili, Dante (Frontiers in Pharmacology, 2020)
Acetylation of histone and non-histone protein lysine residues has been widely described as a critical modulator of several cell functions in humans. Lysine acetyltransferases (KATs) catalyse the transfer of acetyl groups on substrate proteins and are involved in multiple physiological processes such as cell signalling, metabolism, gene regulation, and apoptosis. Given the pivotal role of acetylation, the alteration of KATs enzymatic activity has been clearly linked to various cellular dysfunctions leading to several inflammatory, metabolic, neurological, and cancer diseases. Hence, the use KAT inhibitors (KATi) has been suggested as a potentially successful strategy to reverse or prevent these conditions. To date, only a few KATi have proven to be potential drug candidates, and there is still a keen interest in designing molecules showing drug-like properties from both pharmacodynamics and pharmacokinetics point of view. Increasing literature evidence has been highlighting natural compounds as a wide source of molecular scaffolds for developing therapeutic agents, including KATi. In fact, several polyphenols, catechins, quinones, and peptides obtained from natural sources (including nuts, oils, root extracts, and fungi metabolites) have been described as promising KATi. Here we summarize the features of this class of compounds, describing their modes of action, structure-activity relationships and (semi)-synthetic derivatives, with the aim of assisting the development of novel more potent, isoform selective and drug-like KATi.